Special Education: Challenges for Rural School Systems - A. James Artesani; David W. Brown (Journal of Research in Rural Education, 1998)
This article describes how one rural school systemfacing perceived increasing costsforspecial education, a concern for the impact special education programs have on staffand general education programs, and limited federal, state, and local resources, completed an in-depth analysis of it's special education services. The review process used, the data gathered, and the lessons learned may serve as a guide for other educators and school districtsfacing this or similar issues.